2021
DOI: 10.1111/jasp.12774
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the impact of exposure to scientific role models: Testing an intervention to increase science identity among adolescent girls

Abstract: A field experiment tested an intervention to maximize the impact of a science outreach program by encouraging early adolescent girls (N = 240, Mage =12) to adopt female role models. Girls participated in workshops led by female role models who were scientific experts in their field. Afterward, they were randomly assigned to choose and write about their favorite workshop leader or to write about the first workshop leader. We hypothesized that the intervention would benefit girls who chose and wrote about a favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…Our findings fit with prior research indicating that ingroup role model exposure was positively related to STEM belongingness or motivational beliefs among underrepresented groups (e.g., Casad et al, 2018; Chen & Moons, 2015; Cheryan et al, 2013; Johnson et al, 2019; Merritt et al, 2021; Riegle-Crumb et al, 2017; Shin et al, 2016; Stout et al, 2011). Seeing self-relevant role models may help individuals to discount stereotyped views about women and/or URM persons in pSTEM (i.e., “If you can see it, you can be it”).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings fit with prior research indicating that ingroup role model exposure was positively related to STEM belongingness or motivational beliefs among underrepresented groups (e.g., Casad et al, 2018; Chen & Moons, 2015; Cheryan et al, 2013; Johnson et al, 2019; Merritt et al, 2021; Riegle-Crumb et al, 2017; Shin et al, 2016; Stout et al, 2011). Seeing self-relevant role models may help individuals to discount stereotyped views about women and/or URM persons in pSTEM (i.e., “If you can see it, you can be it”).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, prior research has found stronger feelings of belonging, identity, and motivation beliefs when students experienced ingroup role models (for reviews, see Casad et al, 2018; Lawner et al, 2019). This included same-gender role models (e.g., Merritt et al, 2021; Solanki & Xu, 2018; Stout et al, 2011) or same-race role models (e.g., Johnson et al, 2019; Murray et al, 2009) or both (Pietri et al, 2020). Moreover, a cross-national study of country-level variations in women’s representation in STEM indicated adolescent girls’ math self-concepts were higher in countries with greater gender diversity in STEM (Niepel et al, 2019).…”
Section: Role Models: If You See It Can You Be It?mentioning
confidence: 99%
“…Female role models who led science workshops increased identification with science among early-adolescent girls from underrepresented ethnic backgrounds, even when the role models were from well-represented backgrounds. 55 Lindstrom et al surveyed high school students and educators regarding their perceptions on career and college preparation: participants identified relationships between students and adults who could inspire, guide, and mentor them as one of the most important strategies to support academic readiness. 48 Results from a large meta-analysis of lab and field studies found that students from underrepresented racial/ethnic groups showed improved performance and interest in STEM when exposed to in-group role models; mentors similar in race and ethnicity to their students can have a large impact.…”
Section: Exposure To Role Modelsmentioning
confidence: 99%
“…One factor is that students seeing science professionals ("role models") that reflect students' other, non-science identities may enhance their own science identity. Regarding gender identity, female role models have been shown to positively impact the science identity of female students at the middle school level (Merritt et al, 2021), high school level (Chen et al, 2020), and undergraduate level (Stout et al, 2011;Young et al, 2013). However, it should be noted that some studies have failed to detect a similar effect (Bamberger, 2014;Conner & Danielson, 2016).…”
Section: Science Identity Theorymentioning
confidence: 99%